The Relationship Between Parental Parenting and Student Learning Outcomes In Public High School 6 Padang - Aprilia, Annisa; Yulastri, Asmar; Gusnita, Wiwik; Indrayeni, Wiwik (Universitas Negeri Padang, 2024)
This study is motivated by the researcher's observation of diverse parenting patterns, which even affect student learning outcomes. This study aims to describe parenting patterns, learning outcomes, and analyze the relationship between parenting patterns and student learning outcomes at SMK Negeri 6 Padang. The research method used in this study is to use quantitative methods with a correlational research approach, the population in this study were all grade XI students of SMK Negeri 6 Padang in the 2023/2024 school year totaling 454 students. The sampling technique used was simple random sampling. Data collection is done with google form and using a Likert scale that has been tested for reliability. Data were analyzed with descriptive and correlation analysis. Based on the results of statistical calculations that parental parenting is in the moderate category (53.7%) and the most dominant one used by parents is democratic parenting, student learning outcomes are in the moderate category (35.4%). the results of the research were conducted using Pearson product moment correlation analysis, it is known that the correlation coefficient of parental parenting (X) with learning outcomes (Y) is 0.606 which is included in the strong category. The results of hypothesis testing obtained > namely 3,514> 1,664 and a significance value of 0.001 <0.05. It can be concluded that there is a significant relationship between parenting patterns and student learning outcomes and the hypothesis results are Ha accepted and Ho rejected.